Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1109/tmtt.2002.805169
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced on-wafer time-domain waveform measurement through removal of interconnect dispersion and measurement instrument jitter

Abstract: Abstract-We measure output waveshape and rise time of two high-speed digital circuits on wafer using a 50-GHz prototype of a new instrument. The instrument uses vector error correction to deembed the component under test like a network analyzer, but reads out in the time domain after the fashion of an equivalent-time oscilloscope. With the calibration plane of the instrument set at the tips of the wafer probes, errors arising from dispersion in the connection hardware are removed. We show that the random jitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…(2) (3) (4) The solution of these equations characterizes the port directivity (eoo), port match (ell) and tracking (eloeoi) of the instrument head as shown in reference [5].…”
Section: Calibration and Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) (3) (4) The solution of these equations characterizes the port directivity (eoo), port match (ell) and tracking (eloeoi) of the instrument head as shown in reference [5].…”
Section: Calibration and Correctionmentioning
confidence: 99%
“…It has previously been shown that it is possible to correct for interconnect imperfections in time-domain measurements. In [4] a 2-port, nonlinear Vector Network Analyzer (VNA) measurement was made, and the data presented in traditional time-domain, scalar format. We argue that the most promising approach to realising an instrument with greater bandwidth lies in the encapsulation of a vector-corrected directional signal analyzer in a scope-like format.…”
Section: Introductionmentioning
confidence: 99%